RELIGIOUS LITERACY, ISLAMIC EXCELLENCE, AND CIVIC PLURALITY IN ELITE ISLAMIC SCHOOLS: A MULTIPLE-CASE STUDY IN MEDAN, INDONESIA - Muhammad Irsan Barus; Erlina Erlina; Rodiatul Maghfiroh; Kisno Umbar; Hisyam Fahmi (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2026)
Religious literacy has become an important educational issue in plural societies where religion shapes not only personal belief but also moral formation, citizenship, and public life. This study examines how religious literacy is constructed in selected elite Islamic schools in Medan, North Sumatra, a plural urban context in which Islamic schools are expected to strengthen students’ religious identity while preparing them for social diversity. Drawing on religious literacy theory, the interpretive approach to religious education, and Islamic educational thought, this qualitative multiple-case study addresses a gap in existing literature, which has discussed Islamic schooling in relation to piety, modernization, and middle-class aspiration, but has paid less attention to the specific forms of religious literacy produced by elite Islamic schools in plural urban settings. Data were collected through semi-structured interviews, observation, document analysis, and alumni achievement data review. The findings show that religious literacy in these schools is primarily constructed as practical-normative formation through Qur’anic recitation, tahfiz, congregational prayer, Islamic mentoring, moral discipline, and the internalization of adab. The schools also construct excellence through the integration of Islamic normativity, academic competitiveness, and parental aspirations for moral protection and social mobility. However, plural and civic religious literacy remains less institutionally developed than Qur’anic literacy, worship habituation, and academic achievement. The study demonstrates analytically that Islamic excellence in these schools is constructed through a textual regime of inward-oriented formation, and that plural civic competence constitutes a structural absence within this regime—one that points to the theoretical limits of practical-normative religious literacy in plural democratic societies.